FRUSTRATION AND VERBAL AGGRESSIVE BEHAVIOR AMONG UNIVERSITY STUDENTS WHO PLAY MOBILE LEGENDS: BANG BANG - Ade Christian Dillak; Dewita Karema Sarajar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of competitive online games such as Mobile Legends: Bang Bang has become an integral part of university students’ lives and has introduced complex emotional dynamics in digital interactions. One emotion that frequently emerges during gameplay is frustration, which may be expressed through verbal aggressive behavior. This study aimed to examine the relationship between frustration and verbal aggressive behavior among university students who play Mobile Legends: Bang Bang. The study employed a quantitative approach with a correlational design and involved 250 active university students from various higher education institutions in Indonesia who played Mobile Legends: Bang Bang for at least two hours per day. Data were collected using the Frustration Scale and the Verbal Aggression Scale (VAS), both of which have been adapted into Indonesian. Data analysis was conducted using Pearson correlation analysis. The results revealed a significant positive relationship between frustration and verbal aggressive behavior, with a correlation coefficient of r = 0.665 and p < 0.001, indicating that higher levels of frustration experienced during gameplay are associated with a greater tendency to display verbal aggressive behavior, and conversely, lower levels of frustration are associated with a lower tendency toward verbal aggression. This study implies that emotional regulation, particularly in managing frustration, is an important aspect in minimizing verbal aggressive behavior among university students in the context of competitive online games such as Mobile Legends: Bang Bang.